2018
DOI: 10.1155/2018/2637691
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Efficacy of Triamcinolone Acetonide Iontophoresis versus Topical Calcipotriol/Betamethasone Dipropionate in Treating Nail Psoriasis: A Bilateral Controlled Clinical Trial

Abstract: Background and Objective Psoriasis is a common chronic inflammatory skin disorder affecting any age and gender. The clinical presentation of the nail disease depends on the location of the pathology: nail bed or nail matrix. We aimed to compare the therapeutic effects of triamcinolone acetonide iontophoresis (TI) and topical calcipotriol/betamethasone dipropionate in the nail bed and nail matrix involvements of psoriasis using Nail Psoriasis Severity Index (NAPSI). Materials and Methods In the present bilatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 27 publications
1
12
0
4
Order By: Relevance
“…In 2018, a study conducted by Saki et al compared the therapeutic effects of triamcinolone acetonide iontophoresis (TI) and topical calcipotriol/betamethasone dipropionate. The results demonstrated that there was no difference between effects of TI versus topical therapy in terms of nail bed score ( p = 0.356), matrix score ( p = 0.137), and total NAPSI ( p = 0.098) [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 2018, a study conducted by Saki et al compared the therapeutic effects of triamcinolone acetonide iontophoresis (TI) and topical calcipotriol/betamethasone dipropionate. The results demonstrated that there was no difference between effects of TI versus topical therapy in terms of nail bed score ( p = 0.356), matrix score ( p = 0.137), and total NAPSI ( p = 0.098) [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…The use of galvanic current in the treatment of pathologies with microvascular dysfunction such as hyperhidrosis 27 or nail psoriasis 28 has been widely reported; however, studies of its effectiveness in Raynaud's phenomenon are still scarce. Previous studies 11,29 that used galvanic current in combination with drugs in patients with Raynaud's phenomenon secondary to systemic sclerosis showed that digital skin perfusion increased after a single session.…”
Section: Discussionmentioning
confidence: 99%
“…An average improvement of 72% was observed in the nail psoriasis severity index (NAPSI). Saki et al [ 30 ] investigated 16 patients with nail psoriasis treated with an ointment formulation for 6 months and observed a mean improvement of 55.5% in the NAPSI.…”
Section: Special Locationsmentioning
confidence: 99%
“…ointment appears to be more effective compared to foam in nail psoriasis (no head-to-head data) [ 30 , 31 , 48 ]…”
Section: Figurementioning
confidence: 99%